2020
DOI: 10.17524/repec.v14i4.2574
|View full text |Cite
|
Sign up to set email alerts
|

Influência do Risco de Litígio do Auditor nos Honorários de Auditoria e não Auditoria

Abstract: Objetivo: Analisar o impacto do risco de litígio do auditor nos honorários de auditoria e não auditoria. Método: Realizou-se pesquisa descritiva, documental e com abordagem quantitativa. A população compreendeu as empresas listadas no Estados Unidos da América e a amostra correspondeu a 1.298 empresas para cada ano de análise, que abrangeu o período de 2013 a 2017. Os dados foram coletados e da base de dados da Thomson Reuters Eikon® e analisados por meio da estatística descritiva e de regressão linear m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 34 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…(2017) reported that external auditors charge a litigation premium of about 27% against compensation for the litigation risk against the firms. In another study, Da Silva Giordani et al. (2020) also reported in the US context that a higher litigation risk firms are charged higher non-audit fees by external auditors.…”
Section: Literature Reviewmentioning
confidence: 87%
See 3 more Smart Citations
“…(2017) reported that external auditors charge a litigation premium of about 27% against compensation for the litigation risk against the firms. In another study, Da Silva Giordani et al. (2020) also reported in the US context that a higher litigation risk firms are charged higher non-audit fees by external auditors.…”
Section: Literature Reviewmentioning
confidence: 87%
“…In another study, Da Silva Giordani et al (2020) also reported in the US context that a higher litigation risk firms are charged higher non-audit fees by external auditors. External auditors put greater efforts into auditing those firms that have higher litigation risk, as their extra efforts also increase their remunerations (Da Silva Giordani et al, 2020). Secondly, if any lawsuit declares the corporate to involve in improper management or client-related fraud, then this incident also hampers the auditor's responsibility, performance, and job functions (Da Silva Giordani et al, 2020).…”
Section: Literature Review 21 Conceptual Framework and Hypothesis Dev...mentioning
confidence: 99%
See 2 more Smart Citations